Avaliação da eficácia de um gel com reduzida concentração de fluoreto e suplementado com hexametafosfato em inibir a desmineralização do esmalte dentário: estudo in vitro - Scarpa, Josiane Braga [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The decline of tooth decay in recent decades has been attributed to widespread use of fluoride (F) in various forms of presentation and application. The application of fluoride gel is intended to make the formation of calcium fluoride (CaF2) which would remain in contact with the enamel for a longer period, but its high concentration of F also brings increased risk of acute poisoning. The purpose of this study was to evaluate in vitro whether supplementation of a gel of low concentration of F with hexametaphosphate (HMP) results in an ability to reduce the demineralization of tooth enamel comparable to a standard gel of higher concentration of F. Blocks (n=120) of bovine enamel were selected by measuring the surface hardness (SH1) and divided into six experimental groups (n = 20) treated with the following gels: 1) placebo gel without F and HMP (control group); 2) 9% HMP gel; 3) 4500 μgF/g gel; 4) 4500 μgF/g + 9% HMP gel; 5) 9000 μgF/g gel; 6) 12,300 μgF/g acid gel. The blocks were treated with the respective gels during one minute. Ten blocks of each group were analyzed for concentration of CaF2 formed. The other ten blocks were subjected to five pH-cycling (pH 4.7/ 6h and pH 7.0/18h) during 7 days. After pH-cycling the final surface hardness (SH2) was measured and the percentage of surface hardness alteration was calculated. The concentration of CaF2 retained was also determined. The results were submitted to analysis of variance followed by Bonferroni test (p <0.05). The treatment with gel containing 4,500 μgF/g + 9% HMP resulted in a percentage of surface hardness alteration lower than the non supplemented group (p<0.05) and similar to 9000 μgF/g and acid gel groups (p> 0.05). The concentration of CaF2 formed was higher than non supplemented group, however, lower than 9000 μgF/g and acid gel groups (p> 0.05). The latter showed...

O declínio de cárie dentária nas últimas décadas tem sido atribuído ao amplo uso de fluoreto (F) sob diversas formas de apresentação e aplicação. A aplicação do gel fluoretado visa maior formação de fluoreto de cálcio (CaF2) o qual se manteria em contato com o esmalte durante um período mais prolongado, mas sua alta concentração de F traz também maior risco de intoxicação aguda. O objetivo do presente estudo foi avaliar in vitro se a suplementação de um gel de concentração reduzida de F com hexametafosfato (HMP) resulta numa capacidade em reduzir a desmineralização do esmalte dentário comparável a de um gel padrão de maior concentração de F. Foram selecionados 120 blocos de esmalte bovino através da medida da dureza de superfície (SH1) e divididos em seis grupos experimentais (n=20) tratados com os seguintes géis: 1) gel Placebo, sem F e sem HMP (grupo controle); 2) gel com HMP 9%, 3) gel com 4500 μg F/g, 4) gel com 4500 μg F/g + HMP 9%, 5) gel com 9000 μg F/g, 6) gel com 12300 μg F/g de pH ácido. Os blocos foram tratados uma única vez com os respectivos géis. Dez blocos de cada grupo foram analisados quanto à concentração de CaF2 formado. Os outros dez blocos foram submetidos a cinco ciclagens de pH (pH 4,7- 6h e pH 7,0-18h) durante 7 dias. Após as ciclagens de pH, determinou-se a dureza de superfície final (SH2) para o cálculo da porcentagem de alteração da dureza de superfície.e em seguida, a concentração de CaF2 (retido). Os resultados foram submetidos à análise de variância seguido do teste de Bonferroni (p<0,05). O tratamento com gel contendo 4500 μg F/g + HMP 9% resultou em alteração de dureza de superfície menor do que a do não suplementado (p<0,05) e semelhante a dos grupos 9000 μg F/g e Gel ácido (12300 μg F/g). A concentração de CaF2 formado foi maior que a do grupo...
Keywords: Esmalte dentário; Flúor; Fosfatos; Desmineralização do dente; Dental enamel